EFEKTIVITAS PEMBELAJARAN EKSPLORATIF TENTANG KONSEP DAN PROSES FISIKA DI PERMUKAAN AIR DANAU TONDANO - Djeli Alvi Tulandi; Maria Resbal (Charm Sains: Jurnal Pendidikan Fisika, 2022)
Explorative learning about the concepts and processes of physics on the water surface of Lake Tondano is an example of the process of learning physics by utilizing the natural surroundings as a learning object. The purpose of this study was to determine the effectiveness of exploratory learning about the concepts and processes of physics on the water surface of Lake Tondano. The method used in this research is pre-experimental research with one group pretest-posttest design. This research was conducted through three stages. The first stage is to give a pretest to measure the students' initial abilities. The second stage is to give treatment (treatment) through exploratory learning and the third stage is to give a posttest as a learning evaluation. The research subjects are 2nd-year students at the Manado State University Physics Education Study Program 2021/2022. After obtaining the research data that was processed statistically with the help of SPSS 22.0 for windows. The average pretest result is 51.00 and the posttest result is 90.62. Obtaining N-Gain scores from each student, there are as many as 13 students (overall) in the high N-Gain category with a percentage of 100%. The results of this research that explorative learning about physics concepts and processes on the water surface of Lake Tondano is effectively applied in the physics learning process.